ANALISIS PENERAPAN SISTEM INA-CBG’S RAWAT JALAN GUNA MENUNJANG EFEKTIVITAS KERJA PMIK DI RUMAH SAKIT MUHAMMADIYAH BANDUNG - Aulia Zeta Andhani; Gebi Yanitama (INFOKES (Informasi Kesehatan), 2021)
ABSTRACT This study aims to determine an overview implementation of the outpatient INA-CBG’S system to support work effectiveness of medical recorders and health information at Rumah Sakit Muhammadiyah Bandung. The research method used is a qualitative research method with a descriptive approach. Data collection techniques were participant observation, unstructured interviews, documentation, and questionnaire. From the research results obtained, the descriptive analysis based from the answer on the questionnaire regarding the application of the INA-CBG’S system can be concluded well with the average correspondent 72% was agree. Meanwhile, the effectiveness of work was concluded as good with an average correspondent responses 76% agree. However, there were several problems that arose, including: 1). Incomplete claim submission files; 2). There were problems with pending claims; 3). Bridging a rudimentary system; 4). Maintenance and updating of the system during working hours. The suggestions given by the author to improve the implementation of the outpatient INA-CBG’S system to support work effectiveness of medical recorders and health information at Rumah Sakit Muhammadiyah Bandung were: 1). Holding regular meetings to discuss and findings the case in the application of the INA-CBG’S syste; 2). the registration officers more careful in checking patient files; 3). Doctors give more attention to writing and filling out medical resumes; 4). For the coder, it is necessary to check again in terms of determining the code for diagnosis and procedure; 5). NCC maintenance and updates can be done outside of working hours.